Colorimetric and fluorescent probe for real-time detection of palladium (II) ion in aqueous medium and live cell imaging. (January 2018) - Chen, Xiangzhu; Wang, Hongmei; Ma, Xiaodong; Wang, Mian; Zhang, Yuanyuan; Gao, Gui; Liu, Jingjing; Hou, Shicong
Abstract: A novel fluorescent and colorimetric sensor (WM-S ) was synthesized from coumarin oxime and 2-chloroethyl methyl sulfide in a straightforward manner. The sensor displayed high selectivity for detection of Pd 2+ over other metal ions (Cu 2+ and Hg 2+ in particular). The probe also exhibited high sensitivity for recognition of Pd 2+ in aqueous media and can detect trace amounts of Pd 2+ in real time, with a detection limit as low as 41.5 nM. Fluorescence imaging experiments of Pd 2+ in HeLa cells indicated that the sensor can penetrate cell membranes and effectively detect intracellular Pd 2+ . Graphical abstract: Highlights: A new fluorescent probe that can detect trace amounts of Pd(II) ions in real time in aqueous media was synthesized. The probe displayed the high selectivity towards Pd 2+ over other metal ions (Cu 2+ and Hg 2+ in particular). The probe showed good cell permeability and Pd 2+ could be detected within the cells.